2019
DOI: 10.1109/access.2019.2947472
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Selecting Receptive Field Network for Visual Tracking

Abstract: Recently, Convolutional Neural Networks (CNNs) have shown tremendous potential in the visual tracking community. It is well-known that the receptive field is a critical factor for CNN affecting performance. However, standard CNNs based tracking methods design the receptive fields of artificial neurons in each layer that have the same size. We identify the main bottleneck of affecting the tracking accuracy as regular receptive fields. To settle the problem, we propose an Auto-Selecting Receptive Field Network (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Therefore, it becomes crucial to carefully replace the traditional convolutions with appropriate alternatives. Additionally, experiments have shown that introducing attention mechanisms [ 50 ], image enhancement methods [ 51 ], and enlarging the receptive field [ 52 ] can effectively improve detection performance. Nevertheless, these approaches come with the drawback of increased parameters and the calculation amount, making the deployment of the model challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it becomes crucial to carefully replace the traditional convolutions with appropriate alternatives. Additionally, experiments have shown that introducing attention mechanisms [ 50 ], image enhancement methods [ 51 ], and enlarging the receptive field [ 52 ] can effectively improve detection performance. Nevertheless, these approaches come with the drawback of increased parameters and the calculation amount, making the deployment of the model challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, avoiding repetitive convolution is necessary for small object detection. The research conducted by Zhuang [23] et al showed that the receptive field is a key factor that affects the performance of a CNN, and increasing the receptive field helps to improve the classification task. Lei [24] et al demonstrated that dilated convolution can increase the perceptual field sizes of network layers and effectively expand the corresponding receptive field while retaining the valuable contextual information, providing stronger feature semantic information for the network.…”
Section: Dilated Convolutionmentioning
confidence: 99%
“…At each time slot, each UAV samples a receiver of its transmission from this distribution. Especially, the number of GN operations determines the receptive field of GNN and how far packets can travel along edges in the network, selecting an appropriate receptive field will improve the performance of the method [38]. The receptive field refers to the specific region in the input space that a neuron or a group of neurons in a neural network is sensitive to.…”
Section: Graph Network Blockmentioning
confidence: 99%